Borealization impacts shelf ecosystems across the Arctic - Husson, Bérengère; Bluhm, Bodil A.; Cyr, Frédéric; Danielson, Seth L.; Eriksen, Elena; Fossheim, Maria; Geoffroy, Maxime; Hopcroft, Russell R.; Ingvaldsen, Randi B.; Jørgensen, Lis L.; Lovejoy, Connie; Meire, Lorenz; et al. (Frontiers in Environmental Science, 2024)
Climate change is rapidly modifying biodiversity across the Arctic, driving a shift from Arctic to more boreal ecosystem characteristics. This phenomenon, known as borealization, is mainly described for certain functional groups along sub-Arctic inflow shelves (Barents and Chukchi Seas). In this review, we evaluate the spatial extent of such alterations across the Arctic, as well as their effects on ecosystemlevel processes and risks. Along the inflow shelves, borealization is driven by long-term strengthened inflow of increasingly warm waters from the south and punctuated by advection and low sea ice extreme events. A growing body of literature also points to an emerging borealization of the other Arctic shelf ecosystems, through a "spillover" effect, as local changes in environmental conditions enable movement or transport of new species from inflow shelves. These modifications are leading to changes across functional groups, although many uncertainties remain regarding under-sampled groups, such as microbes, and technical challenges of consistent, regular monitoring across regions. There is also clear consensus that borealization is affecting phenology, species composition, community traits, population structure and essential habitats, species interactions, and ecosystem resilience. Non-dynamic environmental factors, such as depth and photoperiod, are thought to limit the complete borealization of the system, and may lead to intermediate, "hybrid" ecosystems in the future. We expect current borders of Arctic and boreal ecosystems to progress further northward and ultimately reach an equilibrium state with seasonal borealization. Risks to the system are difficult to estimate, as adaptive capacities of species are poorly understood. However, ice-associated species are clearly most at risk, although some might find temporary refuge in areas with a slower rate of change. We discuss the likely character of future Arctic ecosystems and highlight the uncertainties. Those changes have implications for local communities and the potential to support Blue Growth in the Arctic. Addressing these issues is necessary to assess the full scale of Arctic climate impacts and support human mitigation and adaptation strategies.